2016
DOI: 10.1111/cge.12864
|View full text |Cite
|
Sign up to set email alerts
|

Baraitser–Winter cerebrofrontofacial syndrome

Abstract: Baraitser–Winter cerebrofrontofacial syndrome (BWCFF) (BRWS; MIM #243310, 614583) is a rare developmental disorder affecting multiple organ systems. It is characterised by intellectual disability (mild to severe) and distinctive facial appearance (metopic ridging/trigonocephaly, bilateral ptosis, hypertelorism). The additional presence of cortical malformations (pachygyria/lissencephaly) and ocular colobomata are also suggestive of this syndrome. Other features include moderate short stature, contractures, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
(105 reference statements)
0
15
0
1
Order By: Relevance
“…None of our individuals were detected to have agyria/pachygyria or coloboma, which are frequent in BRWS. 30 , 31 This further emphasizes that ACTB loss-of-function mutations cause a specific syndrome distinct from BRWS.…”
Section: Main Textmentioning
confidence: 94%
“…None of our individuals were detected to have agyria/pachygyria or coloboma, which are frequent in BRWS. 30 , 31 This further emphasizes that ACTB loss-of-function mutations cause a specific syndrome distinct from BRWS.…”
Section: Main Textmentioning
confidence: 94%
“…Previous studies focusing on subcortical neuronal heterotopia have shown relationships between cortical lamination and the genetic abnormalities associated with the mechanisms of migration impairment in agyric/pachygyria syndromes (Marcorelles et al, 2010; Verloes et al, 2014; Yates et al, 2017). In this study with associated callosal agenesis and heterotopia, we have demonstrated an array of underlying pathologies, such as impairments in the proliferation of the progenitor cells, a noticeable reduction of neurons, and growth cones without leading edges in the CGE.…”
Section: Discussionmentioning
confidence: 99%
“…Most birth defects have unknown causes (Nelson & Holmes, ); however, there is strong evidence that genetic factors contribute to their etiologies. To date, much of what is known about the genetics of birth defects includes effects of high‐risk alleles that cause rare multiple malformation syndromes (Belmont, Mohapatra, Towbin, & Ware, ; de Munnik et al, ; Lewin, Glass, & Power, ; Maslen, ; Mori & Bruneau, ; Yates, Turner, Firth, Berg, & Pilz, ). Such alleles occur at very low frequency in the general population and explain relatively little of the population burden of birth defects.…”
Section: Other Considerations and Future Directionsmentioning
confidence: 99%